2012
DOI: 10.1007/s00442-012-2507-5
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting resource limitations of marine primary producers: implications for competitive interactions under enriched CO2 and nutrient regimes

Abstract: By signing the Copyright Transfer Statement you still retain substantial rights, such as self-archiving:"Authors may self-archive the author's accepted manuscript of their articles on their own websites. Authors may also deposit this version of the article in any repository, provided it is only made publicly available 12 months after official publication or later. He/ she may not use the publisher's version (the final article), which is posted on SpringerLink and other Springer websites, for the purpose of sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
79
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 87 publications
(86 citation statements)
references
References 59 publications
5
79
1
1
Order By: Relevance
“…both Ulva and Fucus were tested in a biculture experiment to inform community response, where we expect opportunistic Ulva to outgrow Fucus resulting in lower growth rates and tissue quality of Fucus (Connell and Russell, 2010;Falkenberg et al, 2013;Worm and Lotze, 2006). We interpret our results in the context of macroalgal response to climate change and future ecosystem structure.…”
Section: Introductionmentioning
confidence: 80%
See 4 more Smart Citations
“…both Ulva and Fucus were tested in a biculture experiment to inform community response, where we expect opportunistic Ulva to outgrow Fucus resulting in lower growth rates and tissue quality of Fucus (Connell and Russell, 2010;Falkenberg et al, 2013;Worm and Lotze, 2006). We interpret our results in the context of macroalgal response to climate change and future ecosystem structure.…”
Section: Introductionmentioning
confidence: 80%
“…High nutrient treatments resulted in decreased C:N ratios, which increases tissue quality. Falkenberg et al (2013) found that increasing each factor resulted in decreased C:N ratios for turf algae, but only nutrients effectively lowered the C:N in the kelp, Ecklonia radiata. We did not find a significant interaction between acidification and nutrients loading on tissue C:N, similar to Falkenberg et al (2013).…”
Section: Algal Tissue Contentmentioning
confidence: 93%
See 3 more Smart Citations